Toxicity Profiling of Marsilea Minuta Conjugated ZnO Nanoparticles for Therapeutics as Nanomedicine - Bala, N. (Journal of Scientific Research, 2025)
Nanomedicine is widely explored nowadays for the treatment of life-threatening diseases, yet it comes with various challenges and questions. In this regard, the exploration of the sanative effect of nanoparticles on cell viability for therapeutic applications is going to be a highly developing research field. Nanomedicines should be properly screened before they can be proclaimed as future technology. The present study encapsulates the acute and sub-acute toxicological aspects of the Marsilea minuta conjugated ZnO (MM-ZnO) nanohybrids synthesized. Biochemical, hematological, and histopathological analyses were performed to assess the toxicity of the nanocomposite. The toxicological profiles of the nanocomposite were studied in vivo in an experimental animal model (mice). Sub-chronic studies in Swiss albino mice of either sex showed little or no change in the biochemical and hematological parameters in low and middle doses of MM-ZnO nanohybrids. Histopathological data analysis of the high dosage revealed very modest alterations at the tissue level. Thus, this study concludes that the synthesized nanohybrids are safe and non-toxic and can be used as therapeutic nanomedicine.